Der Staat als 'Lender of Last Resort' - oder: Die Achillesferse des Eurosystems - Otto Steiger (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2002)
The renewed interest in the theory of the lender of last resort (LOLR) as well as the missing LOLR in the Eurosystem has triggered a new thesis on the LOLR: not the central bank but the Minister of Finance is the true LOLR. The classical theorists of central banking – Steuart, Thornton, Bagehot and Hawtrey – understood, although with some shortcomings, what is overlooked in modern discourses on the LOLR: there are restrictions for the activities of the central bank. While the central bank can create high-powered money for emergency loans without limit, its capacity to absorb losses is limited by the size of its capital. Therefore, it has to rely on the strength of another institution: the taxing power of the Government. In the Eurosystem the problem of the missing LOLR is twofold: (i) the European Central Bank (ECB) cannot be turned into a LOLR because it is, unlike the national central banks, not a bank of issue and (ii) the central EU government is weak, with strictly limited taxing powers. Therefore, to prevent financial crises in the Eurosystem not only central bank and tax money solutions have to be considered but also how to use private money and money from international institutions.
Keywords: E58; E63; 330; Europäische Wirtschafts- und Währungsunion; Zentralbank; Staat; EU-Staaten; Lender of Last Resort